Identifying Racial Minorities' Nationality: Non-verbal Accent as a Cue to Cultural Group Membership - Alcott, Yvette D.; Watt, Susan E. (Frontiers in Psychology, 2021)
Historically, racial appearance has been a common source of information upon which we categorize others, as have verbal accents. Enculturated nonverbal accents which are detected in facial expressions of emotion, hairstyle, and everyday behaviors, have also been found to exist. We investigated the effects of nonverbal accent on categorization and stereotyping when people are exposed to thin slices of behavior. The effects of racial essentialism, which inclines people to categorize and assess others by race, were also tested. In three studies, Australian participants were shown short, muted videos of target individuals performing everyday behaviors. The targets were of a minority (Asian) racial appearance, but half had been interracially adopted as babies and grew up in the Australian mainstream. The other half were foreign nationals who grew up in Asia. In Studies 1 and 2, Australian participants rated each target as Australian or foreign. In both studies, they correctly identified the targets at above chance levels. In Study 3, participants rated the targets on Australian and Asian stereotype traits. They were not told that some targets were Australian and some were foreign, but they nonetheless rated the congruent stereotypes more strongly. Lay theory of race moderated the effect of nonverbal accent, with a weaker effect among participants who endorsed racial essentialism. These preliminary findings reveal subtle effects of nonverbal accent as a cue to cultural group membership and invite further work into the effects of nonverbal accent on person perception and categorization processes.